Hubungan antara Merokok dengan Terjadinya Disfungsi Ereksi di Komunitas Pasar Tradisional Bersehati Manado Tahun 2023 - Mamuaja, Fransiscus X. S.; Turalaki, Grace L. A.; Tendean, Lydia E. N. (e-CliniC, 2025)
Abstract: More than a third of the population in Indonesia has smoking habit. To date, smoking is identified as a risk factor for many health problems, one of them is erectile dysfunction. This study aimed to evaluate the relationship between smoking and erectile dysfunction among male traders and workers in the Pasar Tradisional Bersehati (traditional market) in Manado. This was an analytical and survey study with a cross-sectional design. Purposive sampling was used for sample selection. The research instruments included interview questionnaires and the IIEF-5 questionnaire. The results obtained 77 males as respondents. The highest percentages were found in age group of 21-30 years (28.6%), senior high school (42.9%), working as trader (84.4%), married (74.0%), and being smoker for >3 years (96.1%). Erectile dysfunction was found in 65 respondents (84.41%), most in the age group of 21-30 years (20 respondents), followed by the age groups of 41-50 years (17 respondents) and 31-40 years (11 respondents). The chi-square obtained a significant relationship between smoking and the occurrence of DE (p=0.021). In conclusion, there is a significant relationship between smoking and the occurrence of DE among the community of Pasar Tradisional Bersehati Manado in year 2023; the majority have mild erectile dysfunction. Keywords: smoking; erectile dysfunction; traditional market Abstrak: Lebih dari sepertiga penduduk Indonesia memiliki kebiasaan merokok. Merokok merupakan salah satu faktor risiko dari banyak masalah kesehatan, salah satunya disfungsi ereksi (DE). Penelitian ini bertujuan untuk mengetahui hubungan antara merokok dengan DE pada pedagang dan tenaga kerja pria di Pasar Tradisional Bersehati Manado. Penelitian ini menggunakan survei analitik dengan desain penelitian potong lintang. Teknik pengambilan sampel menggunakan purposive sampling dan instrumen penelitian menggunakan kuesioner wawancara dan kuisioner IIEF-5. Hasil penelitian mendapatkan 77 responden penelitian (n=77). Persentase tertinggi didapatkan pada usia 21-30 tahun (28,6%), tingkat pendidikan SMA/sederajat (42,9%), pekerjaan sebagai pedagang (84,4%), status kawin (74,0%), dan lama merokok >3 tahun (96,1%). Disfungsi ereksi didapatkan pada 65 responden (84,41%), terbanyak pada usia 21-30 tahun (20 responden) diikuti usia 41-50 tahun (17 responden), dan 31-40 tahun (11 responden). Hasil uji chi-square mendapatkan hubungan bermakna antara merokok dengan kejadian DE (p=0,021). Simpulan penelitian ini ialah terdapat hubungan bermakna antara merokok dengan kejadian disfungsi ereksi pada komunitas Pasar Tradisional Bersehati Manado tahun 2023; mayoritas menderita disfungsi ereksi tipe ringan. Kata kunci: merokok; disfungsi ereksi; pasar tradisional